2010
DOI: 10.1538/expanim.59.95
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary-Adrenal Functions in a Hereditary Hypothyroid (rdw) Rat

Abstract: Abstract:The rdw rat is a hereditary hypothyroid strain isolated from Wistar-Imamichi rats. In the present study, adrenocorticotropic hormone (ACTH) and corticosterone responses to restraint stress (120 min) were examined in rdw adult male rats. ACTH response to restraint stress was higher in rdw rats than in hetero control rats. The plasma concentrations of corticosterone were lower in rdw rats than in control rats during the first 30 min after the onset of stress. Both ACTH and corticosterone responses to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
2
0
0
Order By: Relevance
“…The result of the present study indicated that the restraint stress significantly increased plasma and salivary corticosterone levels ( Fig. 2 ), and our observations agreed with previous studies, reporting plasma corticosterone levels in mice and rats treated with restraint stress [ 9 , 22 , 28 , 29 ]. In humans, saliva, in addition to blood samples, is readily available for the measurement of cortisol in various stress-related studies [ 8 , 13 , 26 ].…”
Section: Discussionsupporting
confidence: 93%
“…The result of the present study indicated that the restraint stress significantly increased plasma and salivary corticosterone levels ( Fig. 2 ), and our observations agreed with previous studies, reporting plasma corticosterone levels in mice and rats treated with restraint stress [ 9 , 22 , 28 , 29 ]. In humans, saliva, in addition to blood samples, is readily available for the measurement of cortisol in various stress-related studies [ 8 , 13 , 26 ].…”
Section: Discussionsupporting
confidence: 93%
“…The corticosterone level was increased by restraint stress treatment during the lactation period. Our observation was comparable with previous studies where plasma corticosterone levels were increased in mice and rats treated with restraint stress [ 9 , 18 , 19 , 26 ]. In addition, the body weight of maternal mice during the stress treatment was decreased by restraint stress as the days passed.…”
Section: Discussionsupporting
confidence: 93%